2021
DOI: 10.31294/par.v8i1.9297
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualisme Di Dua Daya Tarik Wisata Ikonik Di Kawasan Bandung Utara

Abstract: ABSTRAKPentingnya multilingulisme pada aktivitas pariwisata dipicu oleh adanya hambatan komunikasi dan budaya antara pengelola daya tarik wisata dengan wisatawan. Penelitian ini bertujuan untuk mengidentifikasi program-program yang telah dilakukan oleh pengelola daya tarik wisata di Kawasan Bandung Utara. Penelitian ini dilakukan selama empat bulan di tahun 2020 dan dilaksanakan di kawasan pariwisata di Bandung Utara yang difokuskan pada dua daya tarik ikonik yaitu Taman Wisata Alam Gunung Tangkubanparahu dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Tourist attractions or tourist destinations are the 20 main drivers for tourists. Attractions are also prepared in advance so that visitors can see and enjoy them, including dances, regional art songs, traditional ceremonies, and so on (Abdullah & Wulung, 2021;Page et al, 2014). Then it can be concluded that tourist attractions are everything that has been prepared in advance in order to obtain a beauty that has good value in terms of diversity, uniqueness in terms of cultural richness and man-made products, such as dances, traditional folk-art songs, traditional rituals and other tourist attractions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourist attractions or tourist destinations are the 20 main drivers for tourists. Attractions are also prepared in advance so that visitors can see and enjoy them, including dances, regional art songs, traditional ceremonies, and so on (Abdullah & Wulung, 2021;Page et al, 2014). Then it can be concluded that tourist attractions are everything that has been prepared in advance in order to obtain a beauty that has good value in terms of diversity, uniqueness in terms of cultural richness and man-made products, such as dances, traditional folk-art songs, traditional rituals and other tourist attractions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kajian mengenai multilingualisme sudah banyak dikaji oleh beberapa peneliti sebelumnya (Rahayu & Anisah, 2021;Shabudin, 2012;Sudrama & Yadnya, 2015;Wahyudi & Widhiasih, 2016;Abdullah & Wulung, 2021;Yusnia et al, 2022). Penelitian-penelitan terkait mengkaji multilingualisme dari berbagai aspek.…”
unclassified